2016
DOI: 10.12911/22998993/64827
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Urgency of Undertaking Land Consolidation Works in the Villages of the Sławno Municipality

Abstract: The object of the paper is to analyze the spatial structure of land and identification of the needs of consolidation works and exchange of land in the villages of the Sławno municipality, lying in the district of Opoczno, in the Łódzkie Voivodship. The authors use the method of zero unitarisation for the purposes of determining the order of undertaking consolidation works and exchange of land in the area of research. The basis for calculation is the database of 19 factors (x 1 -x 19 ) characteristic for the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…The ranking was established using Hellwig's synthetic indicator of development (Hellwig 1968;Pluta 1968;Bartosiewicz 1976;Krakowiak-Bal 2005). The calculations were carried out using 19 factors describing each of these localities, as selected previously by Leń and Mika (2016b). The results in the form of a synthetic indicator for each village enabled us to create a ranking of priority of land consolidation and exchange interventions.…”
Section: Determination Of the Urgency Of Land Consolidation And Land mentioning
confidence: 99%
See 1 more Smart Citation
“…The ranking was established using Hellwig's synthetic indicator of development (Hellwig 1968;Pluta 1968;Bartosiewicz 1976;Krakowiak-Bal 2005). The calculations were carried out using 19 factors describing each of these localities, as selected previously by Leń and Mika (2016b). The results in the form of a synthetic indicator for each village enabled us to create a ranking of priority of land consolidation and exchange interventions.…”
Section: Determination Of the Urgency Of Land Consolidation And Land mentioning
confidence: 99%
“…Development of agricultural production space, as shown in numerous studies (Wójcik, Leń 2015;Leń, Mika 2016a, 2016b, has resulted in a very faulty structure of ownership of arable land in the examined area. Such an inefficient land ownership structure requires urgent intervention aimed at adjusting land use to the advanced agricultural technologies of the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Due to financial restraints, it is necessary to identify the most defective areas and eliminate them, which will have a positive impact on the construction of a full-featured real property cadastre [15][16][17][18][19][20][21]. For many years studies have been carried out pertaining to comprehensive programming of land consolidation works [22][23][24][25], aiming to develop a universal algorithm for the hierarchization of land consolidation works.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis carried out in the villages of the commune of Sławno (district of Opoczno, Łódź Province) showed that 40.9% of the total surface area of farmland belonging to individual holdings was located in external patchworks, which represented 43.1% of the total number of privately owned plots [LEŃ, MIKA 2016a]. A preliminary study in the village of Brzustowiec, located in the commune of Drzewica showed that 26.9% of the total number of privately owned plots of land (23.8% of all private farmland) in that village belonged to out-of-village owners [LEŃ, MIKA 2016b].…”
Section: Introductionmentioning
confidence: 99%